Remains of two temples from the Sariska Forest Reserve - Temples of India Project Team (Jio Institute, 2024)
Seen here are remains of two temples from the Sariska Forest Reserve. The temple on the left is a restored single shrine that had a Latina Nagara variety shikhara (superstructure). What remains of the temple on the right is only its huge plinths with geometric patterns; above these plinths, there are remnants of pillars.